Potential of floating solar technology in Malaysia - Mohd Alif Saifuddin Jamalludin; Firdaus Muhammad Sukki; Siti Hawa Abu Bakar; Fadzliana Ramlee; Abu Bakar Munir; Nurul Aini Bani; Mohd Nabil Muhtazaruddin; Abdullahi Abubakar Mas’ud; Jorge Alfredo Ardila Rey; Ahmad Syahrir Ayub; Nazmi Sellami (Institute of Advanced Engineering and Science, 2019)
Solar energy is a natural source of energy and is tremendously abundant. The concept of floating solar is to fulfil and to support the existing energy supply in order to enhance the human life. The floating solar exploits the massive availability of ocean region and the severe unavailability of land. The main purpose of this paper is to evaluate the potential of floating solar to be deployed in coastal or infield in Malaysia. It was predicted that such system could generate around 14,530 MWh per annum in Malaysia. It can be concluded that floating solar could be one of the most important ocean structures in the future because it is reliable, flexible and has virtually low cost production comparing with other ocean structures